Maize nutrient translocation on artisanal gold mining soil ameliorated with EFB compost, clay, and lime - Deno Okalia; Iskandar; Budi Mulyanto; Untung Sudadi (UNIVERSITY OF LAMPUNG, 2026)
Artisanal gold mining generally produces coarse-textured soils with low nutrient-holding capacity, which limit plant growth and productivity. Soil reclamation in these conditions necessitates not only improved soil quality but also effective nutrient uptake and allocation within the plant. This study aims to evaluate the effects of oil palm empty fruit bunch (EFB) compost, clay soil, and lime, used as soil conditioners, on the concentrations of N, P, and K in various maize organs grown in soil formerly used for artisanal gold mining. The study was conducted in experimental pots using a completely randomized factorial design (CRF) with three factors: A) EFB compost at 6, 12, and 18 t ha-1; B) clay at 10 and 20%; and C) lime at 0.5 and 1.0 t ha-1. After harvest, maize plants were separated into roots, stems, leaves, and grain, and tissue concentrations of N, P, and K were determined. The results showed clear organ-specific patterns of nutrient accumulation. The highest N concentration was found in the grain (1.95%), the highest P in the roots (0.37%), and the highest K in the leaves (3.07%), all under treatment A3B1C1 (18 t ha-1 of EFB compost, 10% clay, and 0.5 t ha-1 of lime). The findings suggest that using EFB compost, clay soil, and lime together can effectively improve nutrient availability, uptake, and partitioning in maize grown on post-gold mining soil. This strategy has the potential to support the productive reuse of degraded artisanal gold mining land.